Didactic System of Vocational Guidance of Students on the Basis of Dual Education - Mirzaahmadovna, Mirzaraxmonova Shaxnoza (European Journal of Life Safety and Stability (2660-9630), 2021)
This article discusses the didactic system of vocational guidance of students on the basis of dual education, which includes vocational training, education, vocational guidance and what measures extensive coverage of the need to implement